Aging and the relationships between long-axis systolic and early diastolic excursion, isovolumic relaxation time and left ventricular length—Implications for the interpretation of aging effects on e - Peverill, Roger E. (PloS one, 2019)
Both the left ventricular (LV) long-axis peak early diastolic lengthening velocity (e`) and long-axis early diastolic excursion (EDExc) decrease with age, but the mechanisms underlying these decreases are not fully understood. The aim of this study was to investigate the relative contributions to aging-related decreases in e`and EDExc from LV long-axis systolic excursion (SExc), isovolumic relaxation time (IVRT, as a measure of the speed of relaxation) and LV end-diastolic length (LVEDL). The study group was 50 healthy adult subjects of ages 17-75 years with a normal LV ejection fraction. SExc, EDExc, e`and IVRT were measured from pulsed wave tissue Doppler signals acquired from the septal and lateral walls. Multivariate modelling was performed to identify independent predictors of EDExc and e`which were consistent for the septal and lateral walls. EDExc decreased with age and the major determinant of EDExc was SExc, which also decreased with age. There was also a decrease of e`with age, and the major determinant of e`was EDExc. IVRT decreased with age and on univariate analysis was not only inversely correlated with EDExc and e`, but also with SExc. IVRT was only a minor contributor to models of EDExc which included SExc, and was an inconsistent contributor to models of e`which included EDExc. LVEDL decreased with age independent of sex and body size, and was positively correlated with SExc, EDExc and e`. Major mechanisms underlying the decrease in e`seen during aging are the concomitant decreases in long-axis contraction and early diastolic excursion, which are in turn related in part to long-axis remodelling of the left ventricle. After adjusting for the extent of systolic and early diastolic excursion, slowing of relaxation, as reflected in prolongation of the IVRT, makes no more than a minor contribution to aging-related decreases in EDExc and e`.